THE EFFECT OF SOCIAL SUPPORT ON PSYCHOLOGICAL RESILIANCE IN ASYLUM SEEKERS AND REFUGEES (Third Sector Social Economic Review, 2021)
Human beings have had to migrate due to various factors throughout history. Especially in recent years, the number of immigrants in our country has increased considerably. With this increase, the adaptation process has gained importance. For this purpose, this study aims to reveal the effect of perceived social support on the psychological resilience of asylum seekers and refugees who have immigrated to our country. The sample of the study consists of 190 asylum seekers and refugees living in the province of Erzurum. In line with the purpose of the study, the Demographic Information Form regarding the participants, the Multidimensional Perceived Social Support Scale and the Short Form of the Psychological Resilience Scale are included in the research form. The results of the study show that the sub-dimensions of perceived social support, friend and private person, are important predictors on the psychological resilience of refugees and asylum seekers.
Keywords: Asylum seeker; refugee; psychological resilience; social support